(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Today, there is a pressing need to create affordable and efficient technology for agricultural product production and widespread crop care application. In the study, which was carried out in fields that utilized drip irrigation technology, the growth and development of plants were examined when mung beans, peas, and beans were grown in two distinct thicknesses of 166 and 83 thousand plants. The collected data showed that plant height, number of leaves, number of seeds, number of pods, and number of grains in pods are all higher when the number of seedlings is lower. In this instance, there were 166,000 bushels of mung, pea, and bean seedlings as opposed to 83,000 bushels.Number of leaves 3.9; 81.4; 4.0 pieces, number of pods 4.8; 0.9; plant height 4.1; 1.6; 2.8 cm; it was discovered that it was 0.9 pieces more. One plant can produce 11.1, 7.0, 3.1, and 0.4 grains per pod throughout the ripening phase. It was noted that this number of pods was greater than 0.5 units. The investigation’s findings indicate that excessive seedling thickness has a detrimental impact on plants’ ability to grow and develop.